Pengenalan Rumah Adat di Pulau Jawa Sebagai Media Pembelajaran Berbasis VRML - Ari Fitriyanto; Kodrat Iman Satoto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Indonesia is rich in culture, ethnicity which one example is the traditional houses that exist in each province. Introduce Indonesian traditional house to users by using information technology as a medium of information could be one way to preserve the nation's culture. Limitations of the media information about traditional houses that currently can only be enjoyed through pictures or visit the traditional houses directly make society can not know the traditional houses in Indonesia optimally. Therefore we need a media so that people can know more about traditional houses in Indonesia without the need to visit directly into sites or less information such as 2-dimensional images in the book. Application developed is combination between virtual reality and website. Application built using the waterfall method. The virtual technology is embedded in a website that allows users to access them anytime and anywhere. Aplication was developed using VRML (Virtual Reality Modeling Language) and 3ds Max modeling software, and using the programming language PHP, HTML, CSS, and MySQL database. The browser needs Cortona3D Viewer plug-in for displaying three-dimensional file. The results of making this application is an application that utilizes the VRML technology to display traditional house on the island of Java in three dimensions. The results show that this application runs in accordance with the design functionality that has been made.